Minimum Bias Methods in a Priori Rate Making - Wolny-Dominiak, Alicja (Procedury minimalnego obciążenia w taryfikacji a priori, 2009)
Insurance companies specializing in casualty insurance create their own rating systems for setting fair premiums for every risk for different kinds of insurance portfolios. The rating system is mostly based on the data analysis concerning the number and the value of claims for individuals or groups (classes) of insured people within a given portfolio. Based on a given rating system, the premium for a particular risk is calculated in two stages: a priori rating and a posteriori rating. In this paper, the process of a priori rating is analyzed with the emphasis on minimum bias methods used for modelling the rating variables.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 92-101